Exploring Ethnoscience in Science Education: A Systematic Literature Review from 2020-2025 - Ali, Lalu Usman; Suranto, Suranto; Indrowati, Meti (Universitas Islam Negeri (UIN) Mataram, 2025)
This study aims to explore the application of ethnoscience in science education through a systematic literature review from 2020 to May 2025. Ethnoscience, as a culturally-based educational approach, plays a crucial role in contextualizing scientific concepts in students' daily lives. This study employs the PRISMA protocol to ensure traceability and transparency in data collection. Of the 76 articles that met the inclusion criteria, most studies were conducted in Indonesia, focusing on primary and secondary education. The findings reveal that ethnoscience research in science education contributes to improving scientific literacy and 21st-century skills and integrating local wisdom values into pedagogical approaches. However, there remains a lack of cross-country research or intercultural comparisons. This study recommends further research with empirical classroom approaches and cross-cultural studies to enhance the validity and transferability of findings. The results of this review provide valuable insights for curriculum developers, educators, and policymakers to design culturally responsive science learning that aligns with students' sociocultural contexts. The integration of ethnoscience can serve as a strategic approach to promote inclusive education, foster identity awareness, and support the sustainability of local knowledge in formal science curricula.